Reactive lymphoid hyperplasia of the liver in a patient with multiple carcinomas: a case report and brief review. Issue 9 (25th August 2006) - Sato, K; Ueda, Y; Yokoi, M; Hayashi, K; Kosaka, T; Katsuda, S
Abstract : A rare case of reactive lymphoid hyperplasia (RLH) of the liver in a 75-year-old woman admitted to hospital for surgical treatment of gastric, caecal and colon carcinomas is described here. Two nodular lesions in the left and right lobes of the liver were clinically diagnosed as metastatic tumours by computed tomography of the abdomen. A demarcating grey–white mass of size 1.4 cm was observed in a partially resected liver specimen. On examining the lesion microscopically, it was found to be composed of hyperplastic lymphoid follicles, lymphocytes, plasma cells, other inflammatory cells and interlaced hyalinised fibrous tissues. In the portal tracts around the lesion, chronic inflammatory cell infiltrates were seen, but no interface hepatitis or lymphoid follicle was observed. No evidence of monoclonality was observed by immunohistochemistry for B and T cell markers, in situ hybridisation for κ and λ light chains, and polymerase chain reaction analysis of immunoglobulin heavy chains or T cell receptor β and γ gene rearrangements. Bcl-2 immunoreactivity was not observed in the germinal centre. Epstein–Barr virus (EBV) antigen (latent membrane protein-1) and EBV-encoded small RNAs were not detected. A proliferation neither of myofibroblasts nor of cells positive for follicular dendritic cell markers was observed. RLH, formerly known as pseudolymphoma, has been reported of the liver in only 14 cases and is considered to be a differential diagnosis of small nodular lesions of the liver. That RLH has an inflammatory reactive nature, not a neoplastic disposition, and that EBV does not participate in the pathogenesis of RLH is supported by this case.